Profiling of cyclic hexadepsipeptides roseotoxins synthesized in vitro and in vivo: a combined tandem mass spectrometry and quantum chemical study - Jegorov, Alexandr; Paizs, Béla; Zabka, Martin; Kuzma, Marek; Havlícek, Vladimír; Giannakopulos, Anastassios E; Derrick, Peter J (European journal of mass spectrometry (Chichester, England), 2003)
High-performance liquid chromatography and tandem mass spectrometry (HPLC/MS/MS) was used for the detection of cyclic hexadepsipeptides roseotoxins produced by Trichothecium roseum. Roseotoxins were found in both submerged standard cultivation on CzapekDox medium and in vivo cultivation extract obtained from an apple. Roseotoxin chromatographic profiles from these two experiments were compared. Product-ion collision-induced dissociation (CID) spectra obtained on an ion trap (electrospray ionisation, ESI) were used for the identification of natural roseotoxins A, B, C and of minor destruxins A and B. The dissociation behavior of roseotoxins is discussed in terms of a fragmentation scheme proposed for describing the dissociation pathways of cyclic peptides. This scheme involves opening of the cyclopeptide ring via formation of oxazolone derivatives and fragmentation of the resulting linear species, which have a free N-terminus and an oxazolone ring at the C-terminus. Some aspects of this fragmentation scheme are underlined by modeling the dissociation channels of roseotoxin A using quantum chemical calculations. The structures of roseotoxin A and destruxin B were verified by nuclear magnetic resonance (NMR) spectroscopy. Structures of three new minor natural roseotoxins [Val(4)]RosA, [MeLxx(4)]RosA and [MeLxx(4)]RosB were deduced by ion cyclotron resonance Fourier transform mass spectrometry (ICR-FT-MS) and ion trap tandem mass spectrometry by examining the pre-separated roseotoxin fraction.
Keywords: depsipeptidy; Mass Spectrometry; Molecular Structure; Peptides, Cyclic; vysokoúčinná kapalinová chromatografie; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie; hmotnostní spektrometrie; Mitosporic Fungi; mitosporické houby; molekulární struktura; Chromatography, High Pressure Liquid; Depsipeptides; cyklické peptidy